2012
DOI: 10.1186/1472-6882-12-88
|View full text |Cite
|
Sign up to set email alerts
|

Using a Delphi consensus process to develop an acupuncture treatment protocol by consensus for women undergoing Assisted Reproductive Technology (ART) treatment

Abstract: BackgroundAssisted reproductive technologies (ART) are increasingly utilised for resolving difficulties conceiving. These technologies are expensive to both the public purse and the individual consumers. Acupuncture is widely used as an adjunct to ART with indications that it may assist reducing the time to conception and increasing live birth rates. Heterogeneity is high between treatment protocols.The aim of this study was to examine what fertility acupuncturists consider key components of best practice acup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 13 publications
1
32
0
1
Order By: Relevance
“…Previous studies have reported that it is feasible to identify a set of intervention ingredients of acupressure with a high level of agreement through the Delphi process for managing various clinical symptoms [16,17]. This study echoed previous ones in successfully formulating an acupressure protocol through expert consensus.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies have reported that it is feasible to identify a set of intervention ingredients of acupressure with a high level of agreement through the Delphi process for managing various clinical symptoms [16,17]. This study echoed previous ones in successfully formulating an acupressure protocol through expert consensus.…”
Section: Discussionsupporting
confidence: 64%
“…The DT has also been used as a research method in many contexts, such as negotiating the clinical symptoms definition [16] and acupuncture protocol development [17]. The DT was therefore employed in this study to develop an acupressure protocol by expert consensus.…”
Section: Methodsmentioning
confidence: 99%
“…Published acupuncture protocols for patients undergoing IVF vary in the points selected, the frequency and duration of treatment, and the mode of stimulation [16]. This variability further complicates the interpretation of data and hinders our understanding.…”
Section: Introductionmentioning
confidence: 99%
“…This variability further complicates the interpretation of data and hinders our understanding. In 2012, an acupuncture treatment protocol was developed by a Delphi consensus process involving 28 English speaking international and national acupuncturists working in the fertility area involving women undergoing Assisted Reproductive Technology (ART) treatment [16]. This protocol describes the parameters of best practice acupuncture for ART, including a protocol suitable for future research.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] It has also been successfully employed in a number of CHM and acupuncture studies for generating consensus in clinical practice or protocol development. [15][16][17][18][19] Ethical approval was granted in June 2011 by the University of Southampton School of Medicine ethics committee (SOMSEC094.11).…”
Section: Designmentioning
confidence: 99%